Examining Risk and Trust in Student Mobile Banking Adoption: An Extended Technology Acceptance Model Perspective - Rahma, Felinda Aprilia; Ulfah, Siti Zayyana (International Journal of Informatics and Information Systems, 2025)
This study examines the influence of trust, compatibility, satisfaction, perceived risk, and risk acceptance on students’ intention to use mobile banking applications. As mobile banking becomes increasingly popular for its convenience and efficiency, especially among tech-savvy youth, understanding the behavioral factors influencing adoption is crucial. Utilizing an extended Technology Acceptance Model (TAM), this study employs a quantitative approach with multiple linear regression analysis. The dataset, comprising responses from 219 Indonesian university students, was drawn from the "cogent_adoption_m_banking_pls" survey. The results reveal that satisfaction, compatibility, and trust significantly influence students’ intention to use mobile banking, while perceived risk and risk acceptance do not show a significant effect. The model explains approximately 57% of the variance in adoption intention (R² = 0.570), indicating substantial explanatory power. These findings offer valuable insights for mobile banking developers and financial institutions to enhance user satisfaction, align services with user lifestyles, and strengthen trust—key factors for increasing adoption among student users.